Prácticas de crianza de un docente en su rol de padre o madre (2018)
The upbringing practices form a central stage in the education of the children and girls especially if they are being formed by educators, in this sense, this investigation it develops from the qualitative methodology in order to understand the reality of the subjects, its experience and the interaction in the environment which is constituted from reflective workshops and interviews constructed from structured questions, which are reflected in the development and analysis of the methods and dynamics in which the teachers educate its children fundamentally in a pedagogic context. Between the most important results there is observed the existence of pedagogic and cultural processes for the fulfillment of the familiar, educational and social norms that shape the environment of the children and girls, also, of the application and valuation of value and ethical beginning across the treatment of the speech produced by the family